Feasibility of incorporating SO42--ions in zeolite-like matrices based on alkaline aluminosilicate binders - Krivenko, Pavlo; Rudenko, Igor; Konstantynovskyi, Oleksandr; Vaičiukynienė, Danutė (Elsevier BV, 2023)
Factors determining minimization of the influence of sulfate environments on concrete and risk of corrosion of embedded steel reinforcement have been analyzed. Coatings based on alkaline aluminosilicate binders were proposed to prevent transport of the sulfate ions into concrete. The formation of water resistant zeolite-like matrices on the alkaline aluminosilicate binder of the Na2O-K2O-Al2O3-SiO2-H2O system at 20 ± 2 ◦C can be provided by the use of calcium-containing modifying additives. Optimized molar ratios between oxides of binder constituent were SiO2/Al2O3 = 4–5 and K2O/(Na2O + K2O) = 0.15–0.30. The results of the study show that the speed of incorporating sulfate ions in cement matrix of binder from the sulfate environment is dependent upon a cation and ranks as follows: (NH4)2SO4 > MgSO4 > Na2SO4 > CaSO4. Complete protection of concrete against the penetration of sulfates can be reached when the developed coating is applied in a thickness of 3 mm.
Keywords: coating; concrete deterioration; sulfate environment; zeolite-like matrix; water resistance; alkaline aluminosilicate binder